Analisis Kejadian Dan Biaya Kecelakaan Lalu Lintas (Studi Kasus Kota Jambi) - Imam Budy Prastiyo (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2023)
One prominent transportation issue is traffic safety due to the high occurrence of accidents. Accidents can result from various factors such as driver errors, poor road conditions, unfit vehicles, and environmental factors. Polresta Jambi recorded that from 2019 to 2021, there were 200 accidents with 18 accident fatalities. Jambi City, as the economic hub of Sumatra Island, experiences heavy traffic due to its dense population. Traffic accidents are a primary concern in road operational management as they threaten the safety of road users. Traffic accidents have financial implications and can lead to loss of life. The consequences extend to poverty levels due to medical expenses and reduced productivity. This research aims to analyze the occurrence and costs incurred as a result of traffic accidents. The analysis methods used include descriptive analysis and gross output (human capital). The analysis results indicate that the highest number of accidents occurred on the Lingkar Timur 1-2 in 2019, totaling 19 accidents and 4 fatalities, with a total accident cost of IDR 5,541,137,534.